Implementation of Religious Policies In Indonesia In The Context of History and Its Dynamics (International Journal of Scientific Research and Management (IJSRM), 2022)
In the state, the existence of policy is very important. In addition to regulating state life, the policy also aims to find the best way for mutual benefit. Both in the education sector, economy, culture, even the religious sector is not spared from the existence of policies. Although the purpose of the policy is for the common good, but in its implementation often raises pros and cons in the community. This research is intended to know the history of the development of religious policy in Indonesia in terms of implementation and dynamics. This study describes the five periods of implementation of religious policy in Indonesia; namely during the Dutch colonial period, the Independence Period and the old Order, the Reform Era, as well as during the covid-19 pandemic. This study shows the findings of religious policy during the covid-19 pandemic as well as the dynamics that occur in the field, which at the same time becomes a novelty value in this study.